Mitogenomic phylogeny of bee families confirms the basal position and monophyly of Melittidae. (27th December 2020) - Husemann, Martin; Neiber, Marco Thomas; Nickel, Jana; Reinbold, Carla V. M.; Kuhlmann, Michael; Cordellier, Mathilde
Abstract: Bees (Anthophila) represent a critical taxon for the ecosystem service of pollination and hence have received great scientific attention. The more than 20, 000 known species of bees are grouped in seven families. Yet, the relationships between bee families are not entirely clear, and specifically, the position of Melittidae and their monophyly has been discussed in the past. Here, we present the most comprehensive mitogenomic phylogeny of bees including five members of Melittidae from two subfamilies and three tribes. Our results suggest monophyly of the family Melittidae and further support their basal position. The data also support the two subfamilies, but are not in line with current assignment of tribes. Our results show, despite advancement with transcriptomic and whole genomic data, the value of mitochondrial data for the reconstruction of phylogenies.